2014
DOI: 10.7314/apjcp.2014.15.10.4117
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 as a Biological Marker Guiding Management in Malignant Pleural Mesothelioma

Abstract: Background: To determine prognostic value of excision repair cross-complementation 1 (ERCC1) in patients with malignant pleural mesothelioma (MPM). Materials and Methods: The study included 60 patients with MPM who were diagnosed and treated in the Radiation Oncology Department of Kayseri Teaching Hospital and Medical Oncology Department of Erciyes University, Medicine School between 2005 and 2013. By using immunohistochemical methods, ERCC1 expression in biopsy specimens was evaluated. We retrospectively asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Two other studies involving MPM patients treated with either pemetrexed as monotherapy, or combined with platinum did not found any association between ERCC1 expression and treatment response [26,27] ). In the same study, a survival analysis at 1 and 2 years reported higher survival rates in patients with no expression of ERCC1 when compared with patients with positive ERCC1 expression (64 and 49% vs. 40 and 0%, respectively) [28]. Remarkably, we found opposite results, with high ERCC1 expression being marker of increased survival.…”
Section: Ercc1supporting
confidence: 47%
“…Two other studies involving MPM patients treated with either pemetrexed as monotherapy, or combined with platinum did not found any association between ERCC1 expression and treatment response [26,27] ). In the same study, a survival analysis at 1 and 2 years reported higher survival rates in patients with no expression of ERCC1 when compared with patients with positive ERCC1 expression (64 and 49% vs. 40 and 0%, respectively) [28]. Remarkably, we found opposite results, with high ERCC1 expression being marker of increased survival.…”
Section: Ercc1supporting
confidence: 47%
“…Similarlary, Cihan et al, (2014) reported that 36% of patients with negative ERCC1 expression and 54% of patients with positive ERCC1 expression had disease progression . With respect to the course of treatment, the mean OS was determined to be 11.7 in patients who had positive ERCC1 expression, while it was 19.2 in patients with negative ERCC1 expression, suggesting an association between ERCC1 expression and disease prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Malignant pleural mesothelioma (MPM) is an aggressive tumor characterised with difficulty of diagnosis in early stage, poor prognosis, and no effective treatment. MPM has a growing tendency worldwide (Cihan et al, 2014), and its peak incidence is expected to occur between 2015 and 2030 (Neumann et al, 2013). Apart from cisplatin and the antifolates, most single-agent chemotherapy regimens?…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of MPM has a growing tendency worldwide [ 17 ] and is likely to peak between the year 2015 and 2030 [ 18 ]. From July 2005 through June 2014, 833 patients with undiagnosed pleural effusions successfully underwent MT in our institute, 342 (41.1%) patients were confirmed to have malignant pleural effusion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%